TRANSITIONAL JUSTICE AND GENDER (IUS LAW Journal, 2025)
In the aftermath of conflicts, women are often found on the periphery of justice as their voices are often silenced by cultural norms, deeply rooted stereotypes, and expectations of society. This Article aims to explore the often unseen and misunderstood struggles women face in the transitional justice process, struggles that lead to the absence of women from the process that is meant to heal an entire society. These processes, either judicial or non-judicial, are important for addressing human rights abuses, yet the exclusion of women weakens their impact.Transitional justice is not a mere process, it is a collective journey toward healing and reconciliation, which is dependant on the recognition of all victims, particularly women whose experiences are frequently overshadowed. Without the active participation of women, the efforts of transitional justice may be deemed incomplete and ineffective, as the involvement of women is crucial for ensuring meaningful and far-reaching justice, which can only be a reality when women are transformed from silent victims to core contributors to change.
Keywords: Transitional justice, Reconciliation, Women in conflict, Victim participation, Empowerment